Information technology literacy: examples from academia in Chile and Hawaii - Quiroga, Luz M. (2006)
This research describes the challenging task of identifying new required competencies and responding with new ITL programs in two different regions. The first one, in Chile, is part of an Ibero-American initiative, ALFIN (ALFabetizacion en INformacion). The second one, in Hawaii, is part of a nationwide program in the United States, advocated by the American Library Association, the Association of College and Research Libraries, and the American Association of School Libraries, among other agencies. Research findings include the target audience of IT programs; copyright issues; necessary cooperation among domain instructors, education specialists, librarians and technology specialists; tools and systems being considered; and distance education